If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(u + 1) + -9 = 4(u + -1) + 2u Reorder the terms: 6(1 + u) + -9 = 4(u + -1) + 2u (1 * 6 + u * 6) + -9 = 4(u + -1) + 2u (6 + 6u) + -9 = 4(u + -1) + 2u Reorder the terms: 6 + -9 + 6u = 4(u + -1) + 2u Combine like terms: 6 + -9 = -3 -3 + 6u = 4(u + -1) + 2u Reorder the terms: -3 + 6u = 4(-1 + u) + 2u -3 + 6u = (-1 * 4 + u * 4) + 2u -3 + 6u = (-4 + 4u) + 2u Combine like terms: 4u + 2u = 6u -3 + 6u = -4 + 6u Add '-6u' to each side of the equation. -3 + 6u + -6u = -4 + 6u + -6u Combine like terms: 6u + -6u = 0 -3 + 0 = -4 + 6u + -6u -3 = -4 + 6u + -6u Combine like terms: 6u + -6u = 0 -3 = -4 + 0 -3 = -4 Solving -3 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6p-2/7=5p+7/8 | | 4x^2-36=160 | | R+4=2r-16 | | T+8=6 | | 2-20x=162 | | z-15z+6=-3(z+3) | | 10-10=124-31x | | Z+250=-100 | | F-9=-2 | | -3p-8=-9(-6p-10)-8(-7+7P) | | 3n+7=3(n+1)+4 | | R+9=1 | | -6-9x=9x+20 | | -6(m-2)-8m=-2 | | (-4x-2)(x-3)=0 | | |x+3|-4=-1 | | 2(a-2b+4)-4(2a-b)= | | z-64z-19=-49(z+6) | | 3m+5=17 | | 2x-5=7x-2 | | 9n+4=49 | | 5(x-3)=3 | | z^3+z-2=0 | | 3+2[x-5]=11 | | 12(x-5)=48 | | H-10=-8 | | 40=s+3(6) | | U-3=-3 | | 2n-17=5n-10 | | 3(y+4)+y=16 | | 6(x+1)-5x=-4 | | 3(2b+1)-5b=10 |